PENGARUH KUALITAS LAYANAN, KESADARAN MEREK DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA BANK SUMUT MEDAN - Rommel Sitohang; Henri Saragih; Ragu Rahman (Jurnal Ilmiah METHONOMI, 2021)
The purpose of the present study is to determine and analyze the effects of service quality, brand awareness, and customer satisfaction on customer loyalty in PT. Bank SUMUT Medan. This study uses a descriptive method with a quantitative approach. The sample consisted of 100 subjects. The results indicate that service quality has a significant effect on customer loyalty, with t-counted value of 5.304 > t-table value of 1.985, and significance value of 0.000 < alpha (0.05). Brand awareness has a significant effect on customer loyalty, with t-counted value of 3.067 > t-table value of 1.985, and significance value of 0.000 < alpha (0.05). Customer satisfaction has a significant effect on customer loyalty, with t-counted value of 7.052 > t-table value of 1.985, and significance value of 0.000 < alpha (0.05). Service quality, brand awareness, and customer satisfaction simultaneously have a significant effect on customer loyalty, with t-counted value of 52.284 > t- table value of 2.700, and a significance value of 0.000 < alpha (0.05).